PENGARUH INSTAGRAM TERHADAP KETERLIBATAN ORANG MUDA KATOLIK DALAM HIDUP MENGGEREJA DI PAROKI SANTO WILLIBRORDUS CEPU - Widiatmoko, Andreas Danar; Gaudiawan, Antonius Virdei Eresto (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
Instagram is a social media application that is currently a new world, especially for young people. OMK (Youth Chatolic Organization) of Saint Willibrordus Cepu’s Parish took advantage of the opportunity of this media to be a media for reporting for his organization. This research has to analyze the impact of instagram, toward OMK's involvement in church; social media and instagram; the use of instagram social media of young Catholic parish of Saint Willibrordus Cepu; and the impact of the instagram account of Saint Willibrordus Cepu’s parish for the youth involvement in the life of the Church. This research used a quantitative method through the Google Form service that was conducted in November 2019. Respondent in this study were 52 OMK of Saint Willibrordus Cepu’s Parish. Based on the results of the research, instagram is a photo and video sharing application. The youth of Saint Willibrordus Cepu’s Parish has used instagram as a space to share photos of OMK’s activities. OMK's Instagram account has a positive impact on almost all respondents, among others in terms of activeness, cohesiveness and attractiveness of OMK who are less active to be active in Church life.